Green manure combined with reduced nitrogen reduce NH3 emissions, improves yield and nitrogen use efficiencies of rice - Hu, Zhongze; Yang, Daliu; Feng, Yaming; Zhang, Shuanglin; Wang, An; Wang, Qiaozhen; Yang, Yayun; Chen, Chunying; Zhang, Yuefang; Wang, Xian (PeerJ, 2024)
Background Green manure is an important source of organic fertilizer. Exploring green fertilizer and nitrogen fertilizer reduction is important for agricultural production. However, few studies have been conducted, especially on the effects of different green fertilizers along with reduced nitrogen fertilizer application on soil ammonia volatilization emissions, rice yield, and nitrogen fertilizer uptake and utilization. Methods In this study, the effects of different types of green manure and reduced nitrogen fertilizer application on soil ammonia volatilization emissions, aboveground population characteristics of rice, and nitrogen fertilizer uptake and utilization were explored. This study was based on a field-positioning experiment conducted between 2020 and 2022. Six treatments were established: no nitrogen fertilizer application (CK), conventional fertilization in wheat-rice (WR), villous villosa-rice (VvR), vetch sativa-rice (VsR), rapeseed seed-rice (RR), and milk vetch-rice (GR), with a 20% reduction in nitrogen fertilizer application. The amounts of phosphorus and potassium fertilizers remained unchanged. The characteristics of ammonia volatilization loss in rice fields, agronomic traits of rice, yield traits, and nitrogen uptake and utilization were investigated. Results The results indicated a significant difference (P < 0.05) in the impact of different treatments on ammonia volatilization emissions from rice in the two-year experiment. Compared with WR treatment, VvR, VsR, RR, and GR treatments reduced the total ammonia volatilization loss by 23.58 to 39.21 kg ha−1, respectively. Compared with the conventional WR treatment, other treatments increased rice yield by 0.09 to 0.83 t ha−1. GR treatment was significantly higher than other green fertilizer treatments, except for VsR (P < 0.05). It increased the nitrogen uptake of rice by an average of 4.24%–22.24% and 13.08%–33.21% over the two years, respectively. The impact of different types of green manure on the nitrogen uptake and utilization of rice varied greatly, indicating that the combination of green manure and fertilizer is a sustainable fertilization model for crops to achieve high yields. In particular, the Chinese milk vetch as green manure was more beneficial for ammonia volatilization reduction in paddy field and stable grain production of rice.
Keywords: Ammonia volatilization; Green manure and reduced nitrogen fertilizer; Rice growth; Nitrogen fertilizer absorption; Yield